Communities, Streets, and People: A Multi-level Study of the Correlates of Victimization - Uding, Clair (Victims & offenders, 2022)
The current study adds the context of the immediate microgeographic environment (measured as the street segment) to the study of individual victimization. Using residential survey and physical observation data collected on 449 street segments nested within 53 communities in Baltimore, MD, we employ multilevel logistic regression models to examine how individual risky lifestyles, the microgeographic context of the street, and community-level measures influence self-reported property and violent crime victimization. Results confirm prior studies that show that risky lifestyles play a key role in understanding both property and violent crime victimization, and community indicators of disadvantage play a role in explaining violent crime victimization. At the same time, our models show that the street segment (micro-geographic) level adds significant explanation to our understanding of victimization, suggesting that three-level models should be used in explaining individual victimization. The impact of the street segment is particularly salient for property crime.